The Proceedings of the 13th International ACM SIGACCESS Conference on Computers and Accessibility 2011
DOI: 10.1145/2049536.2049573
|View full text |Cite
|
Sign up to set email alerts
|

Supporting blind photography

Abstract: Blind people want to take photographs for the same reasons as others-to record important events, to share experiences, and as an outlet for artistic expression. Furthermore, both automatic computer vision technology and human-powered services can be used to give blind people feedback on their environment, but to work their best these systems need highquality photos as input. In this paper, we present the results of a large survey that shows how blind people are currently using cameras. Next, we introduce EasyS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 12 publications
1
97
0
Order By: Relevance
“…in the capture of good quality photos to make photography more appealing [56]; and to help them preserve memories, express creativity, and socialize [28]. Recent research by Wu et al [61] further shows how a system that automatically integrates accessible alt-text information with Facebook photos allowed blind participants to feel more included and engaged with conversation around photos; and thereby supported their ability to interact with their social network more fully.…”
Section: Design For Richer Social Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…in the capture of good quality photos to make photography more appealing [56]; and to help them preserve memories, express creativity, and socialize [28]. Recent research by Wu et al [61] further shows how a system that automatically integrates accessible alt-text information with Facebook photos allowed blind participants to feel more included and engaged with conversation around photos; and thereby supported their ability to interact with their social network more fully.…”
Section: Design For Richer Social Experiencesmentioning
confidence: 99%
“…For example, computer vision can support the recognition of signs, objects, peoples' faces, or the layout of a space [14,28,46]. Yet, the challenge remains how to identify from all potentially available information about an environment those that is relevant to the person's in-situ ability negotiations; and present it without interrupting the skills of a particular person with VI [cf.…”
Section: Triangulation: Afford Relevant Information Resourcesmentioning
confidence: 99%
“…For example, Apple's iPhone (available on 3GS and later models) now has VoiceOver 1 , Android-powered (starting from 4.0) smartphones now support "Eye-Free" 2 multi-touch interactions, and Nokia has also released a free screen reader in their online application store since October, 2011 3 . Touchscreen devices like iPhone were once thought to be inaccessible to blind users, but well-designed, multi-touch interfaces leverage the spatial layout of the screen and can even be preferred by blind people [8].…”
Section: Related Work 21 Accessibility On Mobile Phonesmentioning
confidence: 99%
“…A number of published articles [1, 3,20,21,24] have shown that blind people take photos for multiple reasons, including sending to remote sighted people for feedback and for general object recognition [3]. Despite this, most current camera interfaces are only marginally accessible, which leads to poor-quality photos that are blurry, tilted or improperly framed.…”
Section: Blind Photographymentioning
confidence: 99%
See 1 more Smart Citation